PEMANFAATAN RESONANSI GELOMBANG UNTUK PEMBANGKIT ENERGI LISTRIK - Hasan Achmad, Nur
In fact that oil energy resources are seriously limited, it force us to search for the alternative new energy resources. The sources of wave energy are the suitable alternative to be considered, because they are renewable and widely available on the whole country. Enlargement of the total energy of the wave could be derived from the resonance process in the basin. Several method had already used for analyzing basin wave resonance, like " Boundary Element Method" (done by Lee, 1970) and "Hybrid Element Method" (done by Mei and Chen, 1975). In this tesis, we use " Finite Element Model with Galerkin's Method" to analyze the wave resonance in the basin. The model predicts the natural resonant period of a basin and calculate the amplification of incident waves. Pressure device is a suitable energy convertion system of a resonant wave condition, because it has a sufficient efficiency and suitable for high amplification.